PLAGIARISME DI KALANGAN MAHASISWA DALAM MEMBUAT TUGAS-TUGAS PERKULIAHAN PADA FAKULTAS TARBIYAH IAIN IMAM BONJOL PADANG - Zalnur, Muhammad (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
The purpose of the study is to describe the types of plagiarism done by the students in finishing their lesson tasks. There are three factors that made students did the plagiarism, namely: (1) take other writings and acknowledge them as their own writing, (2) take ideas from part of othersâ writing and change to own language , and (3) take all parts of writings without changing the ideasÂ and language. The causes of plagiarism are: (1) the development of technology and information and, (2) high lessen studi.